2020
DOI: 10.3390/genes11111367
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genomic Profile of Heterogeneous Long Follow-Up Triple-Negative Breast Cancer and Its Clinical Characteristics Shows DNA Repair Deficiency Has Better Prognostic

Abstract: Triple-negative breast cancer (TNBC) presents a marked diversity at the molecular level, which promotes a clinical heterogeneity that further complicates treatment. We performed a detailed whole exome sequencing profile of 29 Mexican patients with long follow-up TNBC to identify genomic alterations associated with overall survival (OS), disease-free survival (DFS), and pathologic complete response (PCR), with the aim to define their role as molecular predictive factors of treatment response and prognosis. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 101 publications
3
2
0
Order By: Relevance
“…In our cohort none of the patients achieved a complete response with NAC and all of them died within three years. Our findings are consistent with and similar to previously reported mortality rates in Latin America and worldwide [29][30][31].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our cohort none of the patients achieved a complete response with NAC and all of them died within three years. Our findings are consistent with and similar to previously reported mortality rates in Latin America and worldwide [29][30][31].…”
Section: Discussionsupporting
confidence: 93%
“…TNBC patients showed a heterogenous TMB, with an average of 3.8 mutations (range 0.4-8.9). These results are comparable to other studies [31,38]. The treated tumors and recurrences in our cohort had the highest TMB in comparison to primary treatmentnaïve tumor, lymph node, and skin metastasis samples.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, compared with patients of EUR ancestry, patients of EAS ancestry with HER2+ BC and TNBC, as well as patients of SAS ancestry with HER2+ BC, were more likely to have tumors that harbor PIK3CAmut (Figs 2A, 2C and 2E). The ancestry-specific tumor PIK3CAmut prevalences observed across BC subtypes is supported by the findings from studies that sampled substantially fewer participants in Africa, [36][37][38][39] Latin America, [40][41][42][43][44] China or Korea, [45][46][47][48][49][50][51][52] and South Asian countries. [53][54][55][56][57] Inconsistencies between PIK3CAmut prevalences identified in our study and those reported in the literature were observed when sample sizes were small and when differences existed in the clinical characteristics of the populations evaluated and/or assay methodologies.…”
Section: Discussionmentioning
confidence: 72%
“…Bioinformatic analyses were performed using previously described methods 41,42 . Briefly, BWA 43 and GATK 44 were used for alignment and data processing, respectively.…”
Section: Bioinformatic Analysis Of Snv In Tumor Tissuesmentioning
confidence: 99%